Socioeconomic Factors Associated with Non-Adherence to Antihypertensive Treatment Among Older Adults Affiliated to the “Pension 65” Program in Peru - Schutt-Cerdan JA; Marcelo-Lluen Snr YE; Oblitas-Guerrero SM; Gálvez-Díaz NDC; Saintila J (Patient Preference and Adherence)
Juliana Anabella Schutt-Cerdan,1 Yngrid Estrella Marcelo-Lluen,1 Susan M Oblitas-Guerrero,1 Norma Del Carmen Gálvez-Díaz,1 Jacksaint Saintila2 1School of Nursing, Faculty of Health Sciences, Universidad Señor de Sipan, Chiclayo, Peru; 2School of Medicine, Faculty of Health Sciences, Universidad Señor de Sipán, Chiclayo, PeruCorrespondence: Jacksaint Saintila, School of Medicine, Universidad Señor de Sipán, Km 5, Carretera a Pimentel, Chiclayo, Lambayeque, 14001, Peru, Email jacksaintsaintila@gmail.comBackground: Hypertension is one of the leading causes of morbidity and mortality among older adults, and its management largely depends on treatment adherence. Previous studies have shown that socioeconomic factors such as income, education, and access to healthcare can significantly influence adherence. However, little is known about how these factors affect older adults living in extreme poverty in Peru, particularly beneficiaries of the “Pension 65” program. This study aims to explore these associations in a highly vulnerable population.Objective: To identify the socioeconomic factors associated with non-adherence to antihypertensive treatment in older adults enrolled in the “Pension 65” program in Peru.Methods: A cross-sectional and analytical study was conducted among 108 older adults enrolled in the “Pension 65” program in Peru. Participants were selected using non-probabilistic convenience sampling. Data on sociodemographic and economic characteristics were collected through a validated questionnaire, and non-adherence to antihypertensive treatment was self-reported. Logistic regression models were applied to identify factors independently associated with non-adherence.Results: Being male (OR = 28.3, 95% CI: 5.3– 149.7), single (OR = 10.9, 95% CI: 2.501– 48.0), having an incomplete primary education (OR = 7.7, 95% CI: 1.9– 30.5), and being affiliated with the Comprehensive Health Insurance (SIS) (OR = 25.3, 95% CI: 5.3– 119.6) were significantly associated with a higher likelihood of non-adherence to treatment. Furthermore, individuals who had never held formal employment (OR = 4.4, 95% CI: 1.6– 11.8), those with an income below $120 USD per month (OR = 8.8, 95% CI: 2.1– 35.6), and those who did not receive financial support (OR = 3.2, 95% CI: 1.1– 9.3) were more likely to be non-adherent to treatment.Conclusion: The findings indicate that various socioeconomic factors hinder adherence to antihypertensive treatment in this vulnerable population. These results highlight the need for interventions, including public policies aimed at improving health education and strengthening access to healthcare services, particularly for older adults with economic constraints.Keywords: vulnerable populations, hypertension, socioeconomic factors, morbidity, pensions, antihypertensive agents